A Genome-Wide Association Study Identifies rs2000999 as a Strong Genetic Determinant of Circulating Haptoglobin Levels - Froguel,P; Ndiaye,NC; Bonnefond,A; Bouatia-Naji,N; Dechaume,A; Siest,G; Herbeth,B; Falchi,M; Bottolo,L; Gueant-Rodriguez,R-M; Lecoeur,C; Langlois,MR; et al. (PLOS One, 2012)
Haptoglobin is an acute phase inflammatory marker. Its main function is to bind hemoglobin released from erythrocytes toaid its elimination, and thereby haptoglobin prevents the generation of reactive oxygen species in the blood. Haptoglobinlevels have been repeatedly associated with a variety of inflammation-linked infectious and non-infectious diseases,including malaria, tuberculosis, human immunodeficiency virus, hepatitis C, diabetes, carotid atherosclerosis, and acutemyocardial infarction. However, a comprehensive genetic assessment of the inter-individual variability of circulatinghaptoglobin levels has not been conducted so far. We used a genome-wide association study initially conducted in 631French children followed by a replication in three additional European sample sets and we identified a common singlenucleotide polymorphism (SNP), rs2000999 located in the Haptoglobin gene (HP) as a strong genetic predictor of circulatingHaptoglobin levels (Poverall = 8.1610259), explaining 45.4% of its genetic variability (11.8% of Hp global variance). Thefunctional relevance of rs2000999 was further demonstrated by its specific association with HP mRNA levels (b = 0.2360.08,P = 0.007). Finally, SNP rs2000999 was associated with decreased total and low-density lipoprotein cholesterol in 8,789European children (Ptotal cholesterol = 0.002 and PLDL = 0.0008). Given the central position of haptoglobin in manyinflammation-related metabolic pathways, the relevance of rs2000999 genotyping when evaluating haptoglobinconcentration should be further investigated in order to improve its diagnostic/therapeutic and/or prevention impact.